Pemutakhiran Peta di Kawasan Laut Natuna Utara Sebagai Langkah Indonesia Menjadi Poros Maritim Dunia - Rio Atnan Riyadi; Diah Apriani Atika Sari (BELLI AC PACIS, 2019)
This study discusses the actions of the Indonesian Government updating maps in the North NatunaSea Area to make Indonesia a Global Maritime Axis. This study is based on legal research using the legal approach and case approach. Collection of legal materials through library studies and analyzed by deductive methods. The results of the discussion showed that updating maps in the North Natuna Sea could make Indonesia a Global Maritime Axis in terms of Defense, Security, Law Enforcement and Safety at Sea and Maritime Diplomacy based on Indonesian Maritime Policy in accordance with United Nations on The Law of The Sea 1982 ( UNCLOS 1982).